2011
DOI: 10.1055/s-0031-1271960
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and MRI Considerations in Sports-Related Knee Joint Cartilage Injury and Cartilage Repair

Abstract: Cartilage injuries of the knee occur frequently in professional and amateur athletes and can be associated with severe debilitation and morbidity. They are commonly associated with ligament injuries but also may be frequently isolated. Increasing awareness and advances in magnetic resonance imaging (MRI) have led to increasing diagnosis and recognition of these injuries. Articular cartilage is just 2 to 4 mm thick and is avascular, alymphatic, and aneural. It has a limited capacity for healing, and there has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 99 publications
(143 reference statements)
0
12
0
Order By: Relevance
“…Radiographs demonstrated the donor site for these fragments, but underestimated the actual size of the osteocartilaginous piece. CT or MRI is beneficial to determine the sites and degrees of osteochondral injuries [7], but arthroscopy is more visual and allows for treatment. Bradley [8] investigated 5000 patients by arthroscopy and found that various types of osteochondral injuries could be identified through presence of loose osteochondral bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographs demonstrated the donor site for these fragments, but underestimated the actual size of the osteocartilaginous piece. CT or MRI is beneficial to determine the sites and degrees of osteochondral injuries [7], but arthroscopy is more visual and allows for treatment. Bradley [8] investigated 5000 patients by arthroscopy and found that various types of osteochondral injuries could be identified through presence of loose osteochondral bodies.…”
Section: Discussionmentioning
confidence: 99%
“…14 Although injuries in professional sport command the highest level of attention with regard to revenue and impact on careers, increasing participation in amateur sport has increased the importance of MSK radiology to the health of amateur athletes. 15 Between 2007 and 2014, injury-related expenses totaling > €64 million were allocated by the GAA Injury Scheme to 58,038 individual claims, 16 figures that demonstrate both the health and economic importance of sports medicine and MSK radiology in the diagnosis and management of Gaelic games injuries.…”
Section: Musculoskeletal Radiology In Sports Medicine and Gaelic Gamesmentioning
confidence: 99%
“…Since its introduction to musculoskeletal imaging in the early 1980s, MRI has revolutionized diagnostic imaging of the knee. Magnetic resonance imaging has an advantage in diagnosis of meniscus lesions and cartilage injuries particularly in the early detection of grade I and grade II lesions [1,2]. Arthroscopy of the knee has been used since the 1970s as a diagnostic and therapeutic tool in the management of acute, subacute and chronic knee complaints [3].…”
Section: Introductionmentioning
confidence: 99%